DETERMINATION OF THE VIBRATION CHARACTERISTICS OF BRIDGE IN DYNAMIC DIAGNOSIS - Menh, Nguyen Cao; Khang, Pham Xuan (Vietnam Journal of Mechanics, 1998)
On the basis of dynamic diagnosis equipment VDIK-1-10 of Russia and finite element method (FEM), the procedures for finding the exciting places and measurement points of vibration are presented. They give us clear information of diagnostic parameters. After data processing we can determine the dynamic characteristics parameters of the bridge. The parameters obtained are used to updating modeling parameters of FEM and therefore the technical state of the bridge could be estimated. An example for investigation of prestressed concrete bridge with 33 m span and 10m width is illustrated.